2019
DOI: 10.2147/amep.s190187
|View full text |Cite
|
Sign up to set email alerts
|

<p>World Mental Health Day 2018, but how aware are medical students?</p>

Abstract: With the recent global interest in mental health, there has been an increase in the number of people coming forward to discuss the once frowned upon illness. It is true that some progress has been made in terms of establishing an equal footing within the health and social care landscape with the help of various campaigns. However, there is still much work to be done with regards to removing the stigma of mental health within the healthcare sector itself. It is no surprise that mental illness statistics are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A recent systematic review demonstrated that 27.2% of medical students have depressive symptoms, 18 which is considered higher than prevalence (9.3%) in the general population of the same age group 19 . Addressing mental health problems is a crucial component of medical education 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review demonstrated that 27.2% of medical students have depressive symptoms, 18 which is considered higher than prevalence (9.3%) in the general population of the same age group 19 . Addressing mental health problems is a crucial component of medical education 20 …”
Section: Introductionmentioning
confidence: 99%
“…19 Addressing mental health problems is a crucial component of medical education. 20 To date, few studies have focused on the discriminatory ability and item functioning of the UPI. This study aims to employ IRT to examine the performance of each UPI item for mental health status.…”
mentioning
confidence: 99%